Toward a knowledge-synthesis heuristic for sport leaders: the strategic leader synthesis model - Cairney, John; Richard, Veronique; Legg, David (Frontiers in Sports and Active Living, 2024)
Sport management leadership research has predominantly focused on leadership behaviours, particularly transformative leadership, without fully acknowledging the complex, multifaceted nature of leadership within the sports context. This perspective overlooks the reality that sports leaders operate within complex organizations and varied contexts that significantly influence their behaviours. Leadership in sports demands core capabilities in decision-making, communication, and strategic thinking, and a mindset that influences perception, decision-making, and behaviour.Consequently, a singular focus on transformative leadership may undervalue the importance of other attributes. This paper thus argues for a comprehensive leadership framework that integrates behaviours, roles, capabilities, and mindset, and draws insights from business management. By proposing this framework organized across four domains-Context, Roles, Capabilities, and Mindset-this paper aims to foster a deeper understanding of sports leadership dynamics, highlighting the necessity of a holistic approach that considers the interconnectedness of these elements.